Laser assisted electron beam conditioning for free electron lasers - A. A. Zholents (Physical Review Special Topics. Accelerators and Beams, 2005)
A new method for electron beam conditioning in free electron lasers is proposed. It uses the electron beam interaction with a laser light in two wiggler magnets separated by a strong-focusing channel. The effect of the conditioning is illustrated by the example of a hypothetical single-pass, high-gain free electron laser operating in the self-amplified spontaneous emission mode with the x-ray emission at λ_{x}=1.5   Å. The proposed conditioner is relatively compact and can be used as a practical add-on device to short x-ray wavelength free electron lasers.